FOR THE LOVE OF DANCE : The Extraordinary Beginnings of Mr & Mrs Bhaskar - Krish, Abhi; Mukherjee, Sayan (Singapore : WS Education, 2023)
Mr K P Bhaskar and Mrs Santha Bhaskar were cultural leaders who devoted their lives to elevating Indian dance in Singapore. Over the last several decades, they have stood strong in the spotlight for their artistic efforts and immeasurable service to the nation. But as celebrated their achievements may be, what has remained in humble silence is the history of their youth.Born fifteen years apart as Bhaskar Krishna Pillai and Pankyamma Santhamma, it was dance that compelled fate to bring this unlikely couple together. The vivid illustrations in this comic book will take readers back to 1937, to witness their extraordinary journeys unfold through the eyes of a young, impassioned K P Bhaskar.
Keywords: Bhaskar, K. P., -- 1925-2013 -- Childhood and youth -- Comic books, strips, etc; Bhaskar, Santha, -- 1939-2022 -- Childhood and youth -- Comic books, strips, etc; Indian dancers -- Singapore -- Biography -- Comic books, strips, etc; Indian dance -- Singapore -- Comic books, strips, etc; Performing arts -- Singapore -- Comic books, strips, etc; Childhood and youth of a person; Comics (Graphic works)